The relationship between financial ratios, corporate governance and fraudulent financial reporting: evidence from malaysian public listed companies / Haziyah Nazifah Busro - Busro, Haziyah Nazifah (2023)
Fraudulent financial reporting (FFR) has received greater attention worldwide due to the huge financial impact that wiped out billions of dollars. Since investors rely on financial reports in making investment decisions, an increase in fraudulent financial reporting issues corrodes the investors' confidence in the reliability of financial reporting in the financial market. Therefore, this study examines the relationship between financial ratios and FFR, corporate governance mechanisms and FFR, and whether corporate governance mechanisms moderate the relationship between financial ratios and FFR of Malaysian public listed companies (PLCs). The FFR companies are selected from Securities Commission Enforcement Release (SCER) listed by Malaysia's Securities Commission for furnishing false statements. The secondary data was acquired manually from the companies’ financial reports and Eikon DataStream (database). This study used logistic regression analysis to test the research hypotheses, and the finding indicates that asset composition ratio and change in auditor have a positive relationship with FFR; however, the capital turnover ratio has a negative relationship with FFR. In terms of moderation, the finding indicates that board independence as a moderating variable weakens the effects of leverage on FFR while strengthening the effects of asset composition on FFR, and change in auditor that acts as a moderating variable weakens the relationship between capital turnover and FFR. Hence, FFR companies are found to have a higher asset composition ratio, more frequently change their auditors, and are less competitive in generating sales from their total assets than non-FFR companies. We provide policy implications based on these findings since they demonstrate some warning signs as FFR prediction tools for regulators such as Securities Commissions and Bursa Malaysia in tracking and monitoring PLCs; auditors and managers in undertaking preventive action at the initial stage; and investors in implementing proper decisions by screening the potential FFR companies so that the likelihood of FFR could be mitigated. Other than contributing practically by highlighting the factors of FFR as fraud predictors, this study also contributes academically by examining the combination of signalling and agency theories.